Low frequency seismic signals lead to hydrocarbon indication and monitoring tool - Alsalim, Mohammed Saad (Kansas State University, 2011)
Recently, South Rub’ al-Khali Company Limited (SRAK) acquired a preliminary survey in the Saudi’s oil producing area to develop a feasible new hydrocarbon indication and monitoring (I & M) device using low frequency seismic signals. Based on broadband seismometer data, the new Hydrocarbon I & M might predict the possibility of a hydrocarbon basin underneath by way of evaluating the received spectra for an additional energy shell between 2.0-6.0 Hz. Such a study is also referred to as hydrocarbon microtremor analysis and recently some contracting geophysical service companies offer such studies. This report will concentrate on the hydrocarbon microtremor analysis of synchronized signal of one frequency and an extra re-determination possibly at a separate location. The paper reports on several critical likely misconceptions and examines repeatability of hydrocarbon microtremors. This work indicates that signal generated by manmade operations can yield same tremor as that assumed for hydrocarbon reservoirs. Equally important, the presence of surface waves generated by anthropogenic signal indicates frequency limits ranging from 1 to 10 Hertz as a result of isolated surface waves. The difficulty of isolating any presumed hydrocarbon related tremors from ambient noise hamper efforts of understanding and applying microseism signals to hydrocarbon exploration and monitoring. Repeatability study by Peter, H. & Sascha, B. (2008) raised questions regarding the source of hydrocarbon microtremors. For improved chances of isolating the implied hydrocarbon microtremors from manmade tremors and near-surface impacts, the data require precise recording based on three metrics, frequencies above 3 Hz should be conserved, highly sensitive seismometers should be engaged, and the data registering time should be enough to register ‘tremor-free’ readings.
Keywords: Low frequency seismic; Hydrocarbon; Geophysics (0373)